The midnight ride of Paul Revere - Longfellow, Henry Wadsworth, 1807-1882 (National Geographic Society, 1999)
The famous narrative poem recreating Paul Revere's midnight ride in 1775 to warn the people of the Boston countryside that the British were coming.